Photoinduced-reset and multilevel storage transistor memories based on antimony-doped tin oxide nanoparticles floating gate. (22nd October 2021) - Jin, Risheng; Shi, Keli; Qiu, Beibei; Huang, Shihua
Abstract: Recently, antimony-doped tin oxide nanoparticles (ATO NPs) have been widely used in the fields of electronics, photonics, photovoltaics, sensing, and other fields because of their good conductivity, easy synthesis, excellent chemical stability, high mechanical strength, good dispersion and low cost. Herein, for the first time, a novel nonvolatile transistor memory device is fabricated using ATO NPs as charge trapping sites to enhance the memory performance. The resulting organic nano-floating gate memory (NFGM) device exhibits outstanding memory properties, including tremendous memory window (∼85 V), superhigh memory on/off ratio (∼10 9 ), long data retention (over 10 years) and eminent multilevel storage behavior, which are among the optimal performances in NFGM devices based on organic field effect transistors. Additionally, the device displays photoinduced-reset characteristic with low energy consumption erasing operation. This study provides novel avenues for the manufacture of simple and low-cost data storage devices with outstanding memory performance, multilevel storage behavior and suitability as platforms for integrated circuits.